(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2025)
The primary objective of this study is to understand the impact of capital structure financing decisions on the market value of companies listed on the Saudi Stock Exchange. To achieve this objective, the researchers adopted an inductive approach to identify the problem of the study, to formulate its questions, and to review previous literature related to study’s topics, in addition to prepare theoretical framework for the study. Researchers also used descriptive analytical approach to analyze the field study data and test the hypotheses to find results and obtain appropriate recommendations. The researchers prepared questionnaire form, (50) Questionnaires were distributed to study sample within the community of the study which represented by companies listed in Saudi stock of exchange, (100%) collected and analyzed. The study’s findings showed that, Capital structure affects a company’s market value if it obtains financing through long-term debt. In addition, the study finding revealed that Capital structure affects a company’s market value if it relies on equity to obtain the necessary financing. The study recommended that, Companies listed in Saudi stock of exchange should consider Kingdom vision 2030 when planning for their capital structures, so as improve their competitive advantages, for the competition with foreign companies that intend to invest in KSA in light of this vision will increase.